Young endurance training starting age in non-elite athletes is associated with higher proximal aortic distensibility. Issue 1 (9th March 2022) - Ryffel, Christoph P; Eser, Prisca; Marcin, Thimo; Herrsche, Dario; Brugger, Nicolas; Trachsel, Lukas D; Wilhelm, Matthias
Abstract : Objective: Decreased proximal aortic distensibility (AD) is known to significantly predict all-cause mortality and cardiovascular events among individuals without overt cardiovascular disease. This cross-sectional study investigated the association of endurance training (ET) parameters, namely, ET starting age, ET years and yearly ET volume with AD in non-elite endurance athletes. Methods: Healthy, normotensive, male Caucasian participants of a 10-mile race were assessed with a 2D echocardiogram and comprehensive interview. Ascending aortic diameters were measured simultaneously with pulse pressure. Aortic strain, AD and aortic stiffness index were calculated. Predictors of AD were investigated among training parameters by linear regression models corrected for age, resting heart rate, stroke volume index and mean blood pressure. Results: Ninety-two of 121 athletes (aged 42±8 years) had sufficient echocardiogram quality and were used for analysis. ET starting age (range 6–52 years) and years of ET (range 2–46 years) were highly collinear and used in two separate models for AD. Significant factors for AD were ET starting age, 10-mile race time and resting heart rate in model I, and age, years of ET, 10-mile race time and heart rate in model II (all p<0.01). Conclusions: In our cohort of healthy, non-elite, middle-aged runners, AD was significantly higher in athletes with younger ET starting age or more years of ET (in the model adjusted for confounders). In the model with years of ET, age had a negative contribution to AD, suggesting that with older age, the benefit of more years of ET on AD decreased. Future studies assessing the effect of exercise training on arterial properties should include training starting age.